Recent advances in stereoselective 1,2-cis-O-glycosylations - Ishiwata, Akihiro; Tanaka, Katsunori; Ao, Jiaming; Ding, Feiqing; Ito, Yukishige (Frontiers in Chemistry, 2022)
For the stereoselective assembly of bioactive glycans with various functions, 1,2-cis O-glycosylation is one of the most essential issues in synthetic carbohydrate chemistry. The cis-configurated O-glycosidic linkages to the substituents at 2 position of non-reducing side residue of the glycoside, such as α-glucopyranoside, α-galactopyranoside, β-mannopyranoside, β-arabinofuranoside and other rather rare glycosides are found in natural glycans, including glycoconjugate (glycoproteins, glycolipids, proteoglycans, microbial polysaccharides) and glycoside natural products. The way to 1,2-trans isomers is well sophisticated by using the effect of neighboring group participation from the most effective and kinetically favored C-2 substituent such as an acyl group, although highly stereoselective synthesis of 1,2-cis glycosides without formation of 1,2-trans isomer is far less straightforward. Although the key factors that control the stereoselectivity of glycosylation are largely understood since chemical glycosylation was considered to be one of the useful methods to obtain glycosidic linkages as the alternative way of isolation from natural source, strictly controlled formation of these 1,2-cis glycosides is generally difficult. This minireview introduces some of the recent advances on the development of 1,2-cis selective glycosylations including the quite recent developments about glycosyl donor modification, reaction conditions and method for activation of intermolecular glycosylation including bimodal glycosylation strategy for 1,2-cis and 1,2-trans glycosides as well as intramolecular glycosylations including recent applications of NAP-ether mediated intramolecular aglycon delivery.